Application of zeolites for the production of biofuels and furans from hexose sugars in ethanol. - Torres-Olea, Benjamín; Pérez-Merchán, Antonio Manuel; Díaz-Maizkurrena, P.; Requies, Jesús M.; Moreno-Tost, Ramón; Cecilia-Buenestado, Juan Antonio; García-Sancho, Cristina; Maireles-Torres, Pedro Jesús (Elsevier, 2023)
The use of zeolites as catalysts in the transformation of glucose and 5-hydroxymethylfurfural (HMF) into 5-ethoxymethylfurfural (EMF) was evaluated. The behaviour of the catalysts could be explained by their morphology, composition, acid properties and chemical coordination of the active sites. The progress of the reaction was followed by High Performance Liquid Chromatography (HPLC) and 13C Nuclear Magnetic Resonance (NMR). Several intermediates were identified, and a reaction path is proposed. Different cosolvents were also employed in this study to enhance the selectivity towards different possible valuable compounds, and they were found to have a positive influence for the production of EMF and furfural.
Keywords: Energía de biomasa; Catalizadores; 5-hydroxymethylfurfural; 5-ethoxymethylfurfural; Glucose; Dehydration; Etherification; Zeolite